Study on toxicological effect and the mechanism of cadmium in rice and inorganic cadmium on ICR mice. Issue 3 (1st June 2021) - Yin, Xiaoyao; Wu, Qian; Song, Wanying; Yang, Qing; Wu, Yongning; Fang, Min; Gong, Zhiyong
Abstract: Cadmium (Cd) exposure may induce chronic intoxication, but the harm of cadmium in rice to human at chronic low-level Cd exposure remains unclear. This study employed a mouse model to investigate the toxicity and mechanism of cadmium in rice and CdCl2 . After 8-week exposure to Cd (CdCl2 and Cd-contaminated rice), the biochemical indicators and oxidation indicators in the serum and liver of mice were determined, and used mRNA sequencing to investigate the mechanism of different forms of Cd. Results showed that the cadmium concentration of the liver in the CdCl2  + Rice-N group (CdCl2 mixed with feed and normal rice, 0.4mg/kg.bw) was higher than that in the Rice-H group (0.4mg/kg.bw). However, the cadmium concentration of the kidneys in the Rice-H group was higher than that in the CdCl2  + Rice-N group. Our study demonstrated that Cd-treated (Cd in rice and CdCl2 ) ICR mice generated obviously tissues injury, such as the increased biochemical studies, the activity of antioxidant enzymes debasement. Simultaneously, our data also indicated that there existed difference of the hepatic toxicity between Cd in rice and CdCl2 . By means of transcriptomics, we discovered that CdCl2 and Cd in rice may affect different gene expression at the molecular level. We hope to provide some theoretical basis for the revision of food security standards. Graphical abstract: